INTELECTUAL CAPITAL, MARKET CAP DAN PENGARUHNYA TERHADAP PERTUMBUHAN KEUANGAN PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2016-2019 - Andini Nurwulandari (Globalwriting Academica Consulting & Publishing, 2019)
Although measuring data assets involves assessing, development, tracking and managing a variety of intangible variables, they are progressively essential for business performance. The goal of the analysis is to examine the impact on financial output of intellectual capital and market cap. The writer utilizes research data from a total of 9 firms in the study data for 2016-2019 to be used by non-financial listed companies on the Indonesian stock market; the study process is the analysis of panel data. The findings from this study indicated that VACA, VAIC, Market Capital Value Added (MCVA) and Earnings per Share had a favorable and meaningful effect (ROE). Sustainability reporting, however, has little effect on equity returns (ROE).